Antifungal effect, surface roughness, and cytotoxicity of three-dimensionally printed denture base with phytoncide-filled microcapsules: An in-vitro study. (May 2022) - Jeon, Sol; Jo, Ye-Hyeon; Yoon, Hyung-In; Han, Jung-Suk
Highlights: Phytoncide microcapsule and digital light processing can produce denture base with antifungal activity. Denture base with phytoncide microcapsules shows antifungal activity against C. albicans at 4 weeks. Optimal microcapsule concentrations for phytoncide A and B were 6wt% and 15wt%. ABSTRACT: Objectives: To produce three-dimensionally (3D) printed removable denture bases with antifungal activity using microencapsulation of phytochemicals that inhibit Candida albicans growth. Methods: Two types of phytoncide oil extract A and B were micro-encapsulated. The phytoncide-filled microcapsules were mixed with denture base resin for 3D printing with various concentration conditions, and manufactured into the discs by digital light processing. The microcapsule concentrations in 3D-printed discs were 2, 4, 6 and 8wt% for the phytoncide oil A, and 5, 10, 15, 20, and 25wt% for the phytoncide oil B. Nine groups with different microcapsule concentrations and a control group were prepared ( n = 5). Microcapsule-containing 3D-printed denture base resin discs were evaluated in terms of surface roughness, polymerization, antifungal activity, and its persistence against C. albicans, and cytotoxicity. Results: There was no significant difference amongst the surface roughness values of all discs. The polymerization of 3D-printed resin disc with microcapsule was different between phytoncide type A and B. The discs with phytoncide-filled microcapsules at 6wt% for type A and 15wt% for type B showed significant antifungal activities against C. albicans at 4 weeks. All discs were reported to be non-cytotoxic to human gingival fibroblasts. Conclusions: Denture base resin discs with antifungal activities were successfully manufactured using phytoncide micro-encapsulation and digital light processing. Considering the antifungal effect and its persistence, surface roughness, polymerization, and cytotoxicity, the optimal microcapsule concentrations for 3D-printed denture bases were 6wt% and 15wt% for phytoncide A and B, respectively. Clinical significance: Using micro-encapsulation of phytochemicals such as phytoncide oil, denture base resin materials with antifungal activities can be successfully fabricated by digital light processing.